The Growth Performance of Young Archachatina marginata Swaison (African Giant Snail) Fed with Mulberry (Morus alba) and Siam-weed (Chromoleana odorata) Leaf Meal Supplementary Diet - Imran, G.T.; Ogungbile, I.A.; Oyeleye, B. (Pakistan Journal of Nutrition, 2011)
Two of the most costly sources of protein ingredients in livestock feed are soya and fishmeals. These ingredients are now becoming scarce due to their multiple uses, hence the needs for sourcing for substitutes. A six weeks Completely Randomised Design experiment was conducted at the FRIN Snailery unit, Ibadan to evaluate the growth perfomance of Archachatina marginata Swaison on mulberry and chromoleana leafmeals. Thirty (30) young snails of 3-5 weeks old were fed with mulberry and siam-weed leafmeals in addition to the unripe pawpaw fruit. Concentrate feed containing soya and fish meals serves as the control. Average feed intakes, body weight gain, shell length and circumference of snails were the parameters assessed. The results showed that highest feed intake and feed conversion ratio were obtained in chromoleana leafmeal treatment but snails fed with mulberry leafmeal performed best in terms of average body weight gain, shell length and circumference of snails. This indicated that leaves of some tropical plants especially especially mulberry and siam-weed could be used as a good substitutes in snail supplementary ration and help to reduce the cost of production in snail farming.